DIGITALIZATION AND EMERGING ISSUES IN ADULT AND NON-FORMAL EDUCATION FOR SUSTAINABLE DEVELOPMENT - GOGARAM, ASMAU ZARMA (Sokoto Educational Review, 2025)
This paper examines digitalization and emerging issues in adult education for sustainable development. Digitalization in adult education encompasses all processes of transferring traditional teaching and learning materials to online learning platforms, educational apps, multimedia resources, online courses, online assessments, and web seminars/conferences or workshops, transitioning to an electronic model for deployment in educational centers. This transformation has thus far been considered a progressive change in the field of academia. The paper identified challenges that affect the digitalization of adult education; these include inadequate funding, inadequate digital facilities, epileptic power supply, poor internet connectivity, increased costs of digital facilities, lack of digital skills, lack of professionalism, implementation challenges, resistance to change, and systemic corruption. Findings recommend the provision of adequate funding, robust digital infrastructural facilities in all adult education centres, effective power generation and distribution across the country, increased investment in digital technology, subsidized prices for digital facilities for teachers and students, and the provision of tax incentives/reliefs for telecommunications companies to enable them to reduce the costs of digital tools for both teachers and learners. DOI: https://doie.org/10.0218/SER.2025259109